A Comprehensive Analysis of Mechanical Strength and Durability in Cellular Light Concrete Blocks Modified with Multiple Additives - Adnan Khan; Abdul Basit Mansoor; Rabia Liaqat; Rozi Khan; Uzair Ali*; Muhammad Anwar Ullah (Spectrum of Engineering Sciences, 2025)
The multipurpose material, cellular lightweight concrete (CLWC), comprises cement, fly ash, and a foaming agent. The popularity of cellular lightweight concrete can be attributed to its low weight, which lowers the structure's self-weight. With its cementitious qualities and mechanically entrained foam in the cement-based slurry, cellular lightweight concrete (CLWC) is a novel material that has significantly increased in popularity in the construction industry over the past ten years. CLC blocks have poor strength issues while being lightweight concrete with strong water absorption and thermal insulation qualities. CLC blocks are altered with additives like fly ash, silica fume, and marble dust to combat this issue. Due to its low strength, a study reveals that silica fume and marble dust have been utilized in several experiments to increase stability. The samples will undergo compressive strength, thermal conductivity, and water absorption tests. Regarding compressive strength, 3% silica fume and 7% marble dust work well. These findings are based on seven and 28-day curing times, while 14-day curing may be investigated in the future. Keywords: Concrete blocks, Silica fume, foaming agent, Marble dust, Fly ash